Insects and their beneficial microbes - Douglas, A. E. (Angela Elizabeth), 1956- (Princeton University Press, 2022)
"In Insects and their Beneficial Microbes, Angela Douglas, a leading scholar in microbiology and microbiome science, brings together the first synthesis of research in beneficial insect-microbe interactions, looking at a variety of insects and their beneficial microbes and the possible ramifications of insect-microbial interactions in agriculture and medicine. Douglas first provides a foundation for microbe-insect interactions and then discusses the many applications for both insects and humans. She begins by discussing the location of these "microbial partners" (the insect and microbe), how insects acquire certain microbes, and what the microbes specifically do for their hosts. For example, we learn how insects supplement nutrients from their microbial partners that protect them from dangerous pathogens and parasites. Douglas also takes a broader look at the mechanisms underlying these symbiotic interactions and the role evolution has played in their creation. Incorporating recent advances in this burgeoning field, this book looks at the way beneficial microbes can offer solutions to problems caused by pests and disease, with possible applications to the human microbiome and human health"--